Prevalence and associated factors of active trachoma among children in Ethiopia: a systematic review and meta-analysis - Alemu Gebrie; Animut Alebel; Abriham Zegeye; Bekele Tesfaye; Fasil Wagnew (2019)
Abstract Background Trachoma is the commonest infectious cause of blindness. It is prevalent in areas where personal and community hygiene is poor, and it mainly affects deprived and marginalized communities most importantly in Ethiopia. Hence, the aim of this study was to determine the prevalence and associated factors of active trachoma among children in Ethiopia. Method A systematic review and meta-analysis was employed to determine the prevalence of active trachoma and associated factors among children in Ethiopia. We searched databases, including PubMed, Google Scholar, Science Direct, EMBASE and Cochrane Library. To estimate the prevalence, studies reporting the prevalence of active trachoma and its associated factors were included. Data were extracted using a standardized data extraction format prepared in Microsoft excel and the analysis was done using STATA 14 statistical software. To assess heterogeneity, the Cochrane Q test statistics and I 2 test were used. Since the included studies revealed considerable heterogeneity, a random effect meta- analysis model was used to estimate the pooled prevalence of active trachoma. Moreover, the association between factors and active trachoma were examined. Results The result of 30 eligible studies showed that the overall prevalence of active trachoma among children in Ethiopia was 26.9% (95% CI: 22.7, 31.0%). In the subgroup analysis, while the highest prevalence was reported in SNNP (35.8%; 95% CI: 22.7, 48.8), the lowest prevalence was reported in Oromia region (20.2%; 95% CI: 12.2, 28.2). Absence of latrine: OR 6.0 (95% CI 2.0, 17.5), the unclean faces of children: OR 5.5 (95% CI 2.8, 10.9), and no reported use of soap for washing: OR 3.3 (95% CI 1.8, 6.0) have shown a positive association with active trachoma among children. Conclusion From this review, it has been concluded that active trachoma among children is still a public health problem in different districts of Ethiopia. The prevalence of almost all studies are significantly higher than WHO target for elimination. Absence of latrine, unclean faces of children, no reported use of soap for washing are the important factors associated with active trachoma among children.